2013
DOI: 10.1101/gad.229385.113
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-induced asymmetry within ATPase activator ring drives σ54–RNAP interaction and ATP hydrolysis

Abstract: It is largely unknown how the typical homomeric ring geometry of ATPases associated with various cellular activities enables them to perform mechanical work. Small-angle solution X-ray scattering, crystallography, and electron microscopy (EM) reconstructions revealed that partial ATP occupancy caused the heptameric closed ring of the bacterial enhancer-binding protein (bEBP) NtrC1 to rearrange into a hexameric split ring of striking asymmetry. The highly conserved and functionally crucial GAFTGA loops responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 59 publications
(81 reference statements)
9
43
0
Order By: Relevance
“…This follows from our observations that a single peptide binds per hexamer, which necessarily requires an asymmetric interface, and is dependent upon the presence of ADP⅐AlF x or ADP⅐BeF x , which allow the ATPase to adopt multiple nucleotide-bound states. This is consistent with models of other ring-like ATPases, including F 1 ATPase (63), E1 helicase (64), Rho helicase (59), the 26S proteasome (65,66), the bacterial enhancer-binding protein NtrC1 (58), and N-ethylmaleimide-sensitive factor (NSF) (67), which all display asymmetry of the subunits that results in a spiral staircase arrangement of the pore loops. An attractive model is that Vps4 translocates substrate, at least partially, through the central pore, driven by changes in pore loop conformations that propagate around the hexamer ring in concert with the ATP hydrolysis cycle.…”
Section: Discussionsupporting
confidence: 86%
“…This follows from our observations that a single peptide binds per hexamer, which necessarily requires an asymmetric interface, and is dependent upon the presence of ADP⅐AlF x or ADP⅐BeF x , which allow the ATPase to adopt multiple nucleotide-bound states. This is consistent with models of other ring-like ATPases, including F 1 ATPase (63), E1 helicase (64), Rho helicase (59), the 26S proteasome (65,66), the bacterial enhancer-binding protein NtrC1 (58), and N-ethylmaleimide-sensitive factor (NSF) (67), which all display asymmetry of the subunits that results in a spiral staircase arrangement of the pore loops. An attractive model is that Vps4 translocates substrate, at least partially, through the central pore, driven by changes in pore loop conformations that propagate around the hexamer ring in concert with the ATP hydrolysis cycle.…”
Section: Discussionsupporting
confidence: 86%
“…This is not a very rare observation because Lee and Huber (49) reported that Rhizobium meliloti C4-dicarboxylic acid transport protein D cross-links with 54 even without Nt binding. In FlrC, the small asymmetry created in the central pore and their elevated thermal vibration upon AMP-PNP binding probably point toward the generation of local asymmetry upon ATP binding, which may enhance during ATP hydrolysis, as observed previously for the other bEBPs (8,9), although the extent of asymmetry may differ in this case. Dimension of the central pore and disposition of the L1 loops around the central pore would seemingly play a crucial role in causing asymmetry (8,9).…”
Section: Discussionsupporting
confidence: 65%
“…Cross-linking and EM reconstruction studies have recently shown that only one oligomeric assembly of bEBP is sufficient enough to simultaneously bind RNAP-54 and the upstream promoter region using varying numbers of participating L1 loops (2,9,47,48). Notably, 54 binds bEBP and RNAP through its highly conserved regions I and III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PspF ring oligomers are believed to undergo sequential hydrolysis where asymmetry in the intersubunit interactions confers cooperativity in nucleotide binding and catalysis (30). In addition, solution structural studies on ring hexamers of another nonhelical bEBP, NtrC1, revealed that one of the intersubunit interfaces is significantly less tight, which led to a mechanistic model where bEBP planar ring split is necessary to drive interactions with the σ 54 -RNAP holoenzyme and ATPdependent remodeling (31).…”
mentioning
confidence: 99%